The economic relevance of on-site construction activities with the External Thermal Insulation Composite System (ETICS) - Sulakatko, Virgo; Lill, Irene (International Journal of Strategic Property Management, 2019)
The systematic inadequacies of the External Thermal Insulation Composite System (ETICS), which occur during the construction phase, increase the financial risk for stakeholders, while reducing the long-term durability of the facade. The economic effect of on-site shortcomings can be reduced if the most significant on-site activities are recognised. The current paper develops an economic relevance assessment model for on-site construction activities of ETICS to increase economic rationality of resource allocation and emphasise the high-risk systematic shortcomings. The economic assessment model quantifies the financial risk of the on-site degradation factors with the method of modified Failure Mode Effects Analysis (FMEA). The data collection is followed by experts’ judgments and is validated with the Delphi technique. The study reveals that degradation factors in the early phases of construction have the highest relevance due to high costs of repair as well as high occurrence possibility and higher detection difficulty due to rapid coverage. Ninety percent of the shortcomings appear during the first five years of completion of the construction. The on-site failures occurring during the application of mechanical anchors and finishing layer cause the lowest financial risk. The model enables the economic effect of the on-site activities to be prioritised for better resource allocation.